Role of cytokines and nitric oxide in the induction of tuberculostatic macrophage functions - Vera L. Petricevich; Rosely C. B. Alves (Mediators of Inflammation)
The aim of this study was to determine phenotypic differences when BCG invades macrophages. Bacilli prepared from the same BCG primary seed, but produced in different culture media, were analysed with respect to the ability to stimulate macrophages and the susceptibility to treatment with cytokines and nitric oxide (NO). Tumour necrosis factor (TNF) activity was assayed by measuring its cytotoxic activity on L-929 cells, interleukin-6 (IL-6) and interferon γ (IFN-γ) were assayed by enzyme-linked immunosorbent assay (ELISA), whereas NO levels were detected by Griess colorimetric reactions in the culture supernatant of macrophages incubated with IFN-γ , TNF or NO and subsequently exposed to either BCG-I or BCG-S. We found that BCG-I and BCGS bacilli showed different ability to simulate peritoneal macrophages. Similar levels of IL-6 were detected in stimulated macrophages with lysate from two BCG samples. The highest levels of TNF and IFN-γ were observed in macrophages treated with BCG-S and BCG-I, respectively. The highest levels of NO were observed in cultures stimulated for 48h with BCG-S. We also found a different susceptibility of the bacilli to ex ogenous treatm ent w ith IFN-γ and TNF which were capable of killing 60 and 70% of both bacilli, whereas NO was capable of killing about 98 and 47% of BCG-I and BCG-S, respectively. The amount of bacilli proportionally decreased with IFN-γ and TNF, suggesting a cytokine-related cytotox ic effect. Moreover, NO also decreased the viable number of bacilli. Interestingly, NO levels of peritoneal macrophages were significantly increased after cytokine treatment. This indicates that the treatment of macrophages with cytokines markedly reduced bacilli number and presented effects on NO production. The results obtained here emphasize the importance of adequate stimulation for guaranteeing efficient killing of bacilli. In this particular case, the IFN-γ and TNF were involved in the activation of macrophage bactericidal activity.